Fatigue properties of combined friction stir and adhesively bonded AA6082‐T6 overlap joints. Issue 9 (8th July 2020) - Maciel, Ricardo; Bento, Tiago; Braga, Daniel F.O.; da Silva, Lucas F.M.; Moreira, Pedro M.G.P.; Infante, Virgínia
Abstract: Even though friction stir welding (FSW) has been shown to produce high performing butt joints, stress concentration at the weld edges in overlap FSW significantly reduces the performance of these joints. By combining FSW and adhesive bonding into a friction stir (FS) weld bonding, joint mechanical performance is greatly improved. Quasistatic and fatigue strength of the proposed FS weld‐bonding joints was assessed and benchmarked against overlap FSW and adhesive bonding. The characterization of the structural adhesive is also presented, including differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), as well as mechanical characterization with curing temperature. A small process parameter study was made to select proper FSW parameters for AA6082‐T6 overlap FSW and FS weld‐bonded joints. FS weld bonding achieved a significant increase in quasistatic and fatigue strength when compared with overlap FSW, with 79.9% of the fatigue strength of adhesive‐bonded joints at 10 6 cycles, whereas FSW had 41.6%.